Selected results of determining the friction interaction coefficient between crushed stone and polyester strip (Rudarsko-geološko-naftni zbornik, 2017)
In the past twenty years in Croatia, a number of reinforced earth constructions have been built, of which two reinforced earth walls stand out due to their dimensions: Strikići and Sveta Trojica. In the building of these walls, polyester strips were used as reinforcement elements, whereas as fi ll material crushed stone aggregate was used. For designing these constructions, knowledge about the interaction mechanisms between the polyester strip and the soil is required. So far, most of the published studies have been directed to the determination of the friction interaction coeffi cient of the poly-ester strip and the fi ll material which was sand or gravel, whereas tests on the interaction between the geosynthetic strip and the crushed stone aggregate have not been performed. In order to determine the friction interaction coeffi cient between the crushed stone aggregate which is commonly used as fi ll material and the geosynthetic strip, pull-out tests of the polyester strip were carried out. Apart from pull-out tests, large direct shear tests were performed to determine shear strength parameters of crushed stone strength. Predictions from the numerical model were compared to a series of pull-out tests, proving that the numerical model provides reasonable predictions of pull-out behavior.